Effect of Monomers and Deposition Conditions on Capacitive Polymer Films Prepared Using Oxidative Multilayers - Marttila Lauri; Salomäki Mikko; Kivelä Henri; Hassinen Jukka; Granroth Sari; Mäkilä Ermei; Nyman Johan; Lukkari Jukka (AMER CHEMICAL SOC, 2025)
Oxidative layer-by-layer multilayers, consisting of polyphosphate (PP), Ce(IV), and graphene oxide, are a general platform for the electrodeless, spatially resolved deposition of redoxactive and capacitive films of conducting polymers and melanin-type materials. However, the film formation process has not been closely examined. We show that PP plays a crucial role in the structure, stability, and function of the multilayers. Random P-O-P bond cleavage in PP at low pH rapidly decreases the effective chain length and, together with the lower complexing capacity of the Ce(III) species, leads to the dissolution of the oxidative multilayer during the polymer film deposition. The multilayer dissolution takes place during, e.g., poly(3,4-ethylenedioxythiophene) (PEDOT) film formation, and produces a homogeneous polymer film on the substrate. On the other hand, polymerization of 5,6-dihydroxyindole (DHI), an analogue of polydopamine, is carried out at higher pH, and the DHI-melanin film forms only on the outer surface, leaving the bulk of the multilayer intact. This leads to a poor electrical contact between the substrate electrode and the redox-active polymer film. Low pH and long deposition times are, therefore, beneficial for the formation of good-quality redox-active polymer films. PEDOT films prepared using oxidative multilayers have good specific volume and mass capacitance, and good retention of their capacitance. Capacitance spectroscopy revealed the contribution of different dynamic processes and showed that the redox processes limit their capacitance in the 100 ms timescale, restricting the power density of the film. The capacitance of the DHI-melanin films decreases drastically in the same timescale while the capacitance and charge storage capacity values remain higher than those of the PEDOT films. Improving the electrical connection to the substrate using alternative deposition techniques and increasing the film conductivity will make the DHI-melanin films promising components for biodegradable supercapacitors.